The Dynamics of Standardization: Three Perspectives on Standards in Organization Studies - Brunsson, Nils; Rasche, Andreas; Seidl, David (Organization studies, 2012)
This paper suggests that when the phenomenon of standards and standardization is examined from the perspective of organization studies, three aspects stand out: the standardization of organizations, standardization by organizations and standardization as (a form of) organization. Following a comprehensive overview of existing research in these three areas, we argue that the dynamic aspects of standardization are under-represented in the scholarly discourse. Furthermore, we identify the main types of tension associated with standardization and the dynamics they generate in each of those three areas, and show that, while standards and standardization are typically associated with stability and sameness, they are essentially a dynamic phenomenon. The paper highlights the contributions of this special issue to the topic of standards as a dynamic phenomenon in organization studies and makes suggestions for future research.